Mesoporous organosilica nanotubes containing a chelating ligand in their walls - Xiao Liu; Yasutomo Goto; Yoshifumi Maegawa; Tetsu Ohsuna; Shinji Inagaki (APL Materials, 2014)
We report the synthesis of organosilica nanotubes containing 2,2′-bipyridine chelating ligands within their walls, employing a single-micelle-templating method. These nanotubes have an average pore diameter of 7.8 nm and lengths of several hundred nanometers. UV-vis absorption spectra and scanning transmission electron microscopy observations of immobilized nanotubes with an iridium complex on the bipyridine ligands showed that the 2,2′-bipyridine groups were homogeneously distributed in the benzene-silica walls. The iridium complex, thus, immobilized on the nanotubes exhibited efficient catalytic activity for water oxidation using Ce4+, due to the ready access of reactants to the active sites in the nanotubes.